Viologen-templated bromoplumbate: a new in situ synthetic method and energy gap engineering. Issue 31 (12th July 2017) - Sun, Cai; Wang, Ming-Sheng; Zhang, Xian; Zhang, Ning-Ning; Cai, Lin-Rong; Guo, Guo-Cong
Abstract : A new in situ synthesis strategy for viologen-based compounds was developed, which is much milder than the traditional solvothermal method. Abstract : Changing N -substituents to modify energy gaps is important for the diverse applications (photochromism, photocatalysis, etc. ) of viologen-based compounds. In situ N -substitution using alcohols under solvothermal and acidic conditions is an effective and common synthetic method for viologen-templated metal halides. In this work, we found that replacing alcohols with alkenes could reduce the reaction temperature dramatically to room temperature. A new cis / trans -viologen-templated bromoplumbate with a novel 1-D chain structure built by edge-sharing planar [Pb3 Br9 ] 3− oligomers was successfully obtained. This bromoplumbate hybrid has a narrower energy gap compared with bulk PbBr2, which has been well explained by linear optical response spectra calculations and PDOS analysis.